N-acetyl-L-cysteine alleviated the oxidative stress-induced inflammation and necroptosis caused by excessive NiCl2 in primary spleen lymphocytes - Zhang, Xintong; Xu, Lihua; Ma, Wenxue; Shi, Bendong; Liu, Qiaohan; Song, Yinghao; Fang, Cheng; Liu, Pinnan; Qiao, Senqiu; Cai, Jingzeng; Zhang, Ziwei (Frontiers in Immunology, 2023)
Ni (nickel) was widely used in industrial manufacturing and daily life due to its excellent physical and chemical properties. Ni has the potential to harm animals' immune system, spleen is a typical immune organ. As a result, it is critical to comprehend the mechanism of NiCl2 damage to the spleen. To better understand the damage mechanism of Ni on spleen lymphocytes, this experiment used mice spleen lymphocytes as the research object and investigated the effects of different concentrations of NiCl2 exposure as well as intervening with strong antioxidants on them. In our experiment, we first measured the degree of oxidative stress, inflammation, and necroptosis caused by different NiCl2 concentrations. According to the findings, NiCl2 could cause spleen lymphocytes to produce a large number of reactive oxygen species (ROS), which reduced the mRNA level of antioxidant enzyme related genes, the changes in GSH-PX, SOD, T-AOC and MDA, the same to the mitochondrial membrane potential. ROS caused the body to produce an inflammatory response, which was manifested by tumor necrosis factor (TNF-α) in an immunofluorescence experiment, and the mRNA level of related inflammatory genes significantly increased. In the case of caspase 8 inhibition, TNF-α could cause the occurrence of necroptosis mediated by RIP1, RIP3 and MLKL, AO/EB revealed that spleen lymphocytes exposed to NiCl2 had significant necroptosis, and the mRNA and protein levels of RIP1, RIP3 and MLKL increased significantly. Based on the above findings, we added the powerful antioxidant N-acetyl-L-cysteine (NAC) and used hydrogen peroxide (H2O2) as the positive control in subsequent experiments. The findings demonstrated that NAC acted as an antioxidant to reduce oxidative stress, inflammation, and necroptosis caused by NiCl2 exposure. Finally, our findings showed that NiCl2 could cause oxidative stress, inflammation, and necroptosis in mice spleen lymphocytes, which could be mitigated in part by NAC. Our study provided a point of reference for understanding the toxicological effect of NiCl2.